The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.ejvs.2005.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Cutaneous Nerve Injury Following Long Saphenous Vein Surgery

Abstract: This study demonstrates the frequency of nerve injury during primary great saphenous vein surgery. It will be useful for clinicians providing informed consent and may provide a benchmark for comparison with newer techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 7 publications
1
16
0
3
Order By: Relevance
“…Other complications of surgery are nerve injury (7%) and deep vein thrombosis (Ͻ2%). [31][32][33][34][35][36] Because the sclerosant enters the deep venous system, UGFS may be associated with several specific complications such as migraine, temporal brain ischaemia, and scotomas, especially among patients with a foramen ovale. 37 As in surgery, most patients will experience ecchymosis and pain (often described as "a pulling chord") for 1 to 2 weeks after endovenous therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Other complications of surgery are nerve injury (7%) and deep vein thrombosis (Ͻ2%). [31][32][33][34][35][36] Because the sclerosant enters the deep venous system, UGFS may be associated with several specific complications such as migraine, temporal brain ischaemia, and scotomas, especially among patients with a foramen ovale. 37 As in surgery, most patients will experience ecchymosis and pain (often described as "a pulling chord") for 1 to 2 weeks after endovenous therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, stripping of the GSV to the knee level significantly reduces the risk of SNI, however, it does not eliminate it, as there is evidence that this could occur in a rate ranging from 5% to 27%. 1,6 Furthermore, recent studies have shown that the risk for trauma to this nerve should not be considered as a major deterrent to avoid a whole length GSV stripping as its adverse symptoms are gradually regressed postoperatively. 6,7 Motivated by the above contradicting opinions, we performed a prospective study in order to investigate the effect of stripping the below knee GSV segment on varicose vein recurrence and any disability induced after SNI during a 5-year period.…”
mentioning
confidence: 99%
“…1,6 Furthermore, recent studies have shown that the risk for trauma to this nerve should not be considered as a major deterrent to avoid a whole length GSV stripping as its adverse symptoms are gradually regressed postoperatively. 6,7 Motivated by the above contradicting opinions, we performed a prospective study in order to investigate the effect of stripping the below knee GSV segment on varicose vein recurrence and any disability induced after SNI during a 5-year period. This study is based on current guidelines for evaluating the treatment of chronic venous disease (CVD) 8,9 and presents a different approach to this controversial issue in the Journal of Vascular Surgery.…”
mentioning
confidence: 99%
“…2 However, ligation and stripping has been associated with a range of adverse effects such as wound infection, haematoma, lymph leaks, pain, scarring, nerve injury, Deep Vein Thrombosis (DVT) and long post-operative recovery. [4][5][6][7] Conventional non-foam sclerotherapy, is considered faster but less effective than surgical stripping (hereafter, "surgery").…”
Section: Introductionmentioning
confidence: 99%